A problem by Atul Anand Sinha

Level pending

We multiplied four consecutive integers and the result was the same as the product of two consecutive integers.

What are the possible values of the product?


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Atul Anand Sinha
Feb 3, 2014

If we take the consecutive integer numbers 0 , 1 , 2 , 3 0, 1, 2, 3 and 0 , 1 0, 1 , respectively, then the products are equal to zero.

Suppose now that there are integers x x and y y so that

x ( x + 1 ) ( x + 2 ) ( x + 3 ) = y ( y + 1 ) x(x+1)(x+2)(x+3)=y(y+1)

and these products are not equal to zero. Then y < 1 y<-1 or y > 0 y>0 . Note that

x ( x + 3 ) = x 2 + 3 x = ( x 2 + 3 x + 1 ) 1 , and ( x + 1 ) ( x + 2 ) = x 2 + 3 x + 2 = ( x 2 + 3 x + 1 ) + 1 . \begin{aligned} \\ x(x+3)&=x^2+3x=(x^2+3x+1)-1 \text{, and} \\(x+1)(x+2)&=x^2+3x+2=(x^2+3x+1)+1 \text{.} \end{aligned}

Using ( a b ) ( a + b ) = a 2 b 2 (a-b)(a+b)=a^2-b^2 , we get

x ( x + 1 ) ( x + 2 ) ( x + 3 ) = ( ( x 2 + 3 x + 1 ) 1 ) ( ( x 2 + 3 x + 1 ) + 1 ) = ( x 2 + 3 x + 1 ) 2 1 x(x+1)(x+2)(x+3)=((x^2+3x+1)-1)((x^2+3x+1)+1)=(x^2+3x+1)^2-1 .

This means that y ( y + 1 ) y(y+1) is one less than a square number, or in other words: y ( y + 1 ) + 1 = y 2 + y + 1 y(y+1)+1=y^2+y+1 is a square. But we have

y 2 < y 2 + y + 1 < ( y + 1 ) 2 = y 2 + 2 y + 1 , if y > 0 y^2<y^2+y+1<(y+1)^2=y^2+2y+1\text{,}\hspace{17pt}\text{if}y>0

and

( y + 1 ) 2 = y 2 + 2 y + 1 < y 2 + y + 1 < y 2 , if y < 1 (y+1)^2=y^2+2y+1<y^2+y+1<y^2\text{,}\hspace{17pt}\text{if}y<-1 .

This means that unless y ( y + 1 ) = 0 y(y+1)=0 , the number y ( y + 1 ) + 1 y(y+1)+1 is always between two consecutive squares so it cannot be equal to a square. This shows that the original product could only be 0 \boxed{0} .

Correction:

Using ( a b ) ( a + b ) = a 2 b 2 (a-b)(a+b)=a^2-b^2 , we get x ( x + 1 ) ( x + 2 ) ( x + 3 ) = ( ( x 2 + 3 x + 1 ) 1 ) ( ( x 2 + 3 x + 1 ) + 1 ) = ( x 2 + 3 x + 1 ) 2 1 x(x+1)(x+2)(x+3)=((x^2+3x+1)-1)((x^2+3x+1)+1)=(x^2+3x+1)^{2}-1 .

Atul Anand Sinha - 7 years, 4 months ago

Log in to reply

Shouldn't the question be phrased as "How many values can the product attain?"

Bruce Wayne - 7 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...